The Influence of Fashion Trends, Media Exposure, and Community on Korean Wave Lifestyle among College Students - Nurhanifah, Shelly; Supartono, Supartono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research was conducted at Universitas Pelita Bangsa Bekasi City Branch involving 86 students as respondents. The purpose of this study is to explore the influence of fashion trends, media exposure, and community on the Korean wave lifestyle, both partially and simultaneously. The method used in this research is quantitative method. The results showed that fashion trends partially had a significant effect on lifestyle, with a t-count value of 1.854 which is greater than the t-table of 1.663 and a significance value (sig) of less than 0.05. Media exposure partially has a significant effect on lifestyle, with a t-count value of 2.875 which is greater than the t-table 1.663 and a significance value (sig) of less than 0.05. Community partially has a significant effect on lifestyle, with a t-count value of 5.965 which is greater than the t-table 1.663 and sig less than 0.05. Simultaneously, fashion trends, media exposure, and community have a significant effect on lifestyle. The joint effect of fashion trends, media exposure, and lifestyle on Korean wave lifestyle reaches 86%, while the remaining 14% is influenced by other variables. The theoretical implication of these findings is to strengthen the understanding of the factors that influence the Korean wave lifestyle among university students. Meanwhile, the practical implication is to guide educational institutions and related parties to develop strategies and programs that can enhance Korean wave-related lifestyles among university students, as well as pay attention to the importance of managing fashion trends, media exposure, and community participation to improve the quality of students' academic and social experiences.